Building compatible and dynamic character matrices – Current and future use of specimen-based character data. Issue 3 (2nd October 2018) - Henning, Tilo; Plitzner, Patrick; Güntsch, Anton; Berendsohn, Walter G.; Müller, Andreas; Kilian, Norbert
Abstract: Herbarium specimens have always played a central role in plant sciences and constitute the cornerstone for systematic and taxonomy. This role is further strengthened with the ongoing digitisation and growing online-availability of collections all over the globe. The increasing usability of specimens demands, however, an improved use and sustainable handling of specimen data not only in new scientific uses correlated with the digitisation, but also by modern workflows applied to the traditional purpose of specimens. A crucial step in the comparative analyses of organisms is the preparation of a character matrix to observe and assess the morphological extent and variability of taxa on the basis of individual specimens. This process and the resulting matrix often are of ephemeral nature since only its results are published in a condensed form. The data relationships are usually not stored, making a re-use impossible and a new analysis inevitable. To overcome the limitations of conventional taxonomy, we here introduce a comprehensive workflow that is currently being implemented on the EDIT Platform for Cybertaxonomy.